Gender Bias of Compliment Responses in Instagram - PUTRI JAVANI, RAYVANA (Language Horizon: Journal of Language Studies, 2016)
Abstrak Tanggapanpujianadalahsebuahtindakandarimenanggapipujian yang diberikan.Perempuandanlaki-lakimempunyaicara yang berbedadalammenanggapipujian. Biasanyalaki-lakimemilikitanggapanpujian yang lebihsingkatdariperempuan.Tujuandaripenelitianiniuntukmenganalisadengancaraapalaki-lakidanperempuanmenanggapipujiandengancara yang berbeda. Penelitianinimenggunakanteoridari Homes (1995) tentangtanggapanpujian, Coates (2005) danLakoff (2004) tentangkarakteristik Bahasa perempuandanlaki-laki, dan Eckert (2003) and Weatherall (2002) tentangalasanmengapalaki-lakidanperempuanberkomunikasidengancara yang berbeda. Penelitianinimenggunakanmetodekualitatifuntukmenganalisa data. Data di penelitianini di ambildali media sosialbernama Instagram, yang terdapatseksikomen. Padaseksikomen, adasebuahpujiandantanggapanpujian.Poinutamadadarihasildalampenelitianiniadalahlaki-lakidanperempuanmenanggapipujiandengancara yang berbedaberdasarkankarakteristiknya. Karakteristiktersebutadalah empty adjective vs neutral adjective, no sense of humor vs sense of humor, hedges, super polite form vs non polite form, hypercorrect grammar vs incorrect grammar, aggravated directives vs mitigated directives. Kata Kunci: pujian, tanggapanpujian, gender, Instagram Abstract Compliment response is an act of responding a given compliment. Women and men have different way when responding to the compliment. Men usually have a shorter compliment response than women. The aim of this research is to find in what way do males and females respond to the compliment differently. This study uses the theory from Holmes (1995) about compliment response, Coates (2005) and Lakoff (2004) about the characteristics of men and women language, and Eckert (2003) and Weatherall (2002) about the reason why men and women speak differently.This study uses qualitative method to analyze the data. The data of this study were taken from a social media called Instagram which has comment section. In the comment section, there is a compliment and compliment response. There is one point of result in this study. That is male and female speaker are different in responding to the compliment based on their characteristics. Those characteristics are empty adjective vs neutral adjective, no sense of humor vs sense of humor, hedges, super polite form vs non polite form, hypercorrect grammar vs incorrect grammar, aggravated directives vs mitigated directives. Keyword: compliment, compliment response, gender, instagram.